Persepsi Mahasiswa, Dosen dan Bidan Pembimbing tentang Model Pembelajaran Klinik Kebidanan yang Ideal - Yanti Yanti; Ova Emilia; Mora Claramita (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: A large number graduates of midwife even now accompanied with low competency isues in associated with quality of clinical learning. Now implementation of clinical learning with caseload model has problems. Clinical learning model in clinical practice that student, teacher and clinical midwife experienced provide greater insight to develop an effective clinical teaching strategy in midwifery education. The main objective of this study was to investigate student midwife, teacher and clinical midwife’ insight about an ideal clinical learning model in midwifery education.Method: A qualitative study by Focus Group Discussion (FGDs). By selected randomly, this study was conducted 32 from 76 final year midwifery students at Estu Utomo Boyolali Midwifery Academy, 14 lecturer and 13 clinical midwife who involve in Estu Utomo Boyolali Midwifery Academy clinical practice program at 2013-2014. There are 4 groups of student midwife, 2 groups of lecturer and 2 groups of clinical midwife. FGDs were arranged in 3 session differently between students, lecturer and clinical midwife. FGDs were facilitated by researcher and 3 research assistant. Data were analyzed using Atlas.Ti 6.1 software to support the coding process and identifying the main categories from verbatim transcripts.Results: Six themes emerged from the focus group data, “student caseload”, “duration of clinical practice”, “clinical placement”, “clinical mentorship”, “documentation”, and “clinical assessment”. From the sixth themes, demonstrated that an ideal clinical learning model in midwifery education to design preparation clinical learning should consider about that components. An ideal clinical learning model in midwifery education should give priority to quality than quantity especially to suggest decreasing student caseload.Conclusion: This study showed that midwife student, teacher and clinical midwife suggest that clinical learning model should give priority to quality than quantity to gain midwifery care competence. Clinical learning model therefore applied with student case loading that each student have different need. They are suggest that midwifery clinical learning should be consistent with the midwifery care philosophy “women center care” that provide midwifery continuity of care.